BENCH-SCALE PRODUCTION OF L-ASPARAGINASE FROM ERWINIA CAROTOVORA IN A LABORATORY FERMENTER: Pharmaceutical Science-Biotechnology - DEVI, SARITA; KULSHRESHTHA, ADITYA; KUMAR RAI, ASHUTOSH; AZMI, WAMIK (International Journal of Life Science and Pharma Research, 2012)
The discovery that L-asparaginase acts as an antitumor agent in children with lymphoblastic leukemia led to the extensive studies on the physicochemical properties of the enzyme as well as on clinical effect. In the present study, attempts were made to optimize various culture parameters for the production of Lasparaginase by Erwinia caratovora MTCC 1428 in a bench scale fermenter. Different sets of physical parameters were designed to enhance the production of L-asparaginase at minimum cost and time. The optimized condition for maximum production of cell mass of E. carotovora MTCC 1428 and maximum Lasparaginase activity obtained were 300 rpm and 0.5 vvm, respectively without pH control. The maximum L-asparaginase activity and maximum cell mass of E. carotovora MTCC 1428 achieved during this fermentation studies was 0.176 U/mg dcw and 1.465 mg/mL at 8 h and 18 h, respectively. The biosynthesis of L-asparaginase was increased 1.98 fold in optimized physical parameters.